Desarrollo de actividades didácticas multimedia complementarias en el software educativo para el área de estudios sociales del nivel de educación general básica, enmarcado a los hechos históricos geográficos educativos del cantón Saraguro - Chalán Saca, Ángel Israel (2016)
This investigative process is called, DEVELOPING ADDITIONAL MULTIMEDIA EDUCATIONAL ACTIVITIES IN THE EDUCATION SOFTWARE FOR THE AREA OF SOCIAL STUDIES GENERAL BASIC EDUCATION LEVEL, WITHIN THE EDUCATION OF CANTON GEOGRAPHICAL HISTORICAL FACTS SARAGURO resulted Educational Software for Social Studies subject eighth year of basic general education of the Educational Units "Fray Cristobal", "Inti Raymi", "Inka Samana" Canton Saraguro, which implemented it as a teaching resource in the process of learning of the topics due to the limited knowledge of the training they have on the use of educational software. The scientific method whose technique was the survey of 55 students and 19 teachers of the mentioned educational institutions, for it was developed based on the specific objective was used: To identify the issues of greatest degree of learning difficulty consisting in the educational software as instructional support in the area of social studies basic general education level, geographic framed historical facts and educational Canton Saraguro, resulting that a large percentage of ignorance in matters of historical facts. Besides the MECS methodology for the development of complementary activities in the educational multimedia software for the area of social studies the level of basic education, framed geographical and historical facts educational Canton Saraguro applied. To prepare and develop educational software, an important tool used, as is, Exe-learinig, Hot potatoes, Edilim this is a didactic tool that uses multimedia resources. The multimedia content developed in the Educational Software for rescuing address issues of cultural identity in education.